Olfactory Dysfunction in Patients With Coronavirus Disease 2019: A Review - Wei, Guoli; Gu, Jialin; Gu, Zhancheng; Du, Cheng; Huang, Xiaofei; Xing, Haiyan; Li, Lingchang; Zhang, Aiping; Hu, Xingxing; Huo, Jiege (Frontiers in Neurology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic is wreaking havoc on public-health and economic systems worldwide. Among the several neurological symptoms of patients with COVID-19 reported in clinical practice, olfactory dysfunction (OD) is the most common. OD occurs as the earliest or the only clinical manifestation in some patients. Increasing research attention has focused on OD, which is listed as one of the main diagnostic symptoms of severe acute respiratory syndrome-coronavirus-2 infection. Multiple clinical and basic-science studies on COVID-19-induced OD are underway to clarify the underlying mechanism of action. In this review, we summarize the clinical characteristics, mechanisms, evaluation methods, prognosis, and treatment options of COVID-19-induced OD. In this way, we hope to improve the understanding of COVID-19-induced OD to aid early identification and precise intervention.